Associations of cerebrospinal fluid profiles with severity and mortality risk of amyotrophic lateral sclerosis - Fu, Jiajia; Lai, Xiaohui; Wei, Qianqian; Chen, Xueping; Shang, Huifang (Frontiers in Neuroscience, 2024)
The relationship between routine cerebrospinal fluid (CSF) testing and the disease phenotype of amyotrophic lateral sclerosis (ALS) is unclear, and there are some contradictions in current studies.This study aimed to analyze the relationship between CSF profiles and disease phenotype in ALS patients. We collected 870 ALS patients and 96 control subjects admitted to West China Hospital of Sichuan University. CSF microprotein, albumin, IgG, index of IgG (IgGindex), albumin quotient (QALB), and serum IgG were examined.In ALS patients, CSF IgG, and QALB were significantly increased, while CSF IgGindex was decreased, compared with control subjects. Approximately one-third of ALS patients had higher CSF IgG levels. The multiple linear regression analysis identified that CSF IgGindex was weakly negatively associated with ALS functional rating scale revised (ALSFRS-R) scores (β = -0.062, P = 0.041). This significance was found in male ALS but not in female ALS. The Cox survival analyses found that upregulated CSF IgG was significantly associated with the increased mortality risk in ALS (HR = 1.219 (1.010-1.470), P = 0.039).In the current study, the higher CFS IgG was associated with increased mortality risk of ALS. CSF IgGindex may be associated with the severity of ALS. These findings may be sexspecific.